إطار مقترح لتطوير دور الأجهزة الرقابية في تقويم أنظمة الرقابة الداخلية بالمؤسسات الحكومية الليبية - الكاديكي حمد علي (Scientific Journal of University of Benghazi, 2020)
This study aims to propose a framework for developing the role of supreme audit institutions in evaluating internal control systems in Libyan governmental institutions, in accordance with relevant professional and international standards, which illustrate the way of performing the audit task by the supreme audit institutions. This is can be achieved via uniting their efforts to contribute to institutional reform and achieve the best performance indicators. To this end, the deductive inductive approach was conducted. One of the key findings of the study is that it proposed a framework that includes two proposals to develop the role of supreme audit institutions in evaluating internal control systems in government institutions. This can be achieved by using combination of elements which are represented in the supreme audit institutions, its vision and its report. These elements are supposed to be combined altogether, so that the first proposal is based on the need to segregation of duties as well as there should be coordination and complementary and mutual cooperation between all the supreme audit institutions. As for the second proposal, it is based on the necessity of merging the various supreme audit institutions into a single regulatory body with integrated expertise. According to the mentioned results, this study suggests the necessity that the supreme audit institutions, represented by the Audit Bureau, to adopt one of these two proposals, either focusing on the necessity segregation of duties so that the tasks of each regulatory body are clearly and explicitly defined in a way that prevents interference and duplication in carrying out their roles as well as to ensure that their duties are complementary to each other. The alternative proposal is by emphasizing the need to merge supreme audit institutions into one solid and integrated body of expertise, and finally, the coordination and cooperation between the supreme audit institutions and internal auditing in the governmental units.